Phytochemical Characterisation of Sorbus Species: Unveiling Flavonoid Profiles Related to Ploidy and Hybrid Origin - Emina Korić; Violeta Milutinović; Alma Hajrudinović-Bogunić; Faruk Bogunić; Tatjana Kundaković-Vasović; Irma Gušić; Jelena Radović Selgrad; Kemal Durić; Haris Nikšić (Plants)
The genetic, morphological and taxonomic diversity of the genus Sorbus is due to homoploid and polyploid hybridisation, autopolyploidy and apomixis, which also influence the production and diversity of secondary metabolites, especially flavonoids. The aim of this study was to investigate the relationships and variations of flavonoids in terms of hybrid origin and ploidy level between the parental species and their hybrid derivatives. The sampling design included leaf material of the following Sorbus accessions from ten natural localities: parental taxa (di-, tri- and tetraploids of S. aria; diploid S. torminalis and S. aucuparia) and their di-, tri- and tetraploid hybrid derivatives from crosses of S. aria × S. torminalis (subg. Tormaria) as well as the tetraploid S. austriaca and S. bosniaca, which originate from crosses of S. aria × S. aucuparia (subg. Soraria). We analysed the flavonoid profiles from the leaf fractions by LC-MS. A total of 23 flavonoids were identified, including apigenin and luteolin derivatives, which distinguish the hybrid groups from each other. This profiling highlights the distinctiveness of the Tormaria and Soraria accessions and emphasises the potential of the subg. Tormaria for further research on bioactive compounds in biological studies.